ANALISIS PENGARUH SOSIAL EKONOMI TERHADAP KESEJAHTERAAN MASYARAKAT KAMPUNG PIGAPU - Herman Yosep Mayabubun; Niswatun Hasanah, Rahmat Arapi (CV. Adiba Aisha Amira, 2025)
This study aims to determine the socio-economic influence on the welfare of Pigapu village. Data collection techniques used to obtain data in this study are observation and questionnaire. Data analysis in this study used multiple linear regression test analysis . From the results of the analysis that has been done, the results show that social and economic have a positive and significant eflect on health, income and consumption.